Effect of Intercropping of the Cover Crop and Peanut on the Growth and Yield of Cassava that Grown by No-Ridging in the Highlands of Rattanak Mondul District, Battambang Province - Valyseavmey Thuok; Chhanun Nil; Mardy Serey (Yayasan Adra Karima Hubbi, 2024)
This article focuses on the practice of conservation agriculture, mainly on soil fertility, soil erosion reduction, soil erosion, and cover crop studies. The study highlights the need for additional support to encourage conservation agriculture adoption, particularly for small-scale farmers. Support measures should include financial assistance to cover initial costs and secure land tenure to promote long-term investments. Despite these advantages, several challenges hindered conservation agriculture adoption. Especially after eliminating tillage and banning herbicides, farmers faced challenges with weed management in the first two years. But conservation agriculture practices improved soil structure by eliminating tillage, which enhanced water retention and drainage, helping crops withstand extreme climate events such as the 2013 flash floods and the 2012 and 2014 droughts. Limited access to affordable conservation agriculture equipment, such as no-till planters, further complicates adoption. Since most farmers prefer to grow cassava, it is easy to grow, but it was too long, so it may take a long time for farmers to plant the next crop, so in this study we conducted a study with planting by adding or inter-kind of crop such as cover crop and peanuts in cassava that no-ridging to find out the benefits of peanuts and cover crop, peanuts acting as a secondary crop after cassava. For data collection research, data analysis methods were taken from the collection of biomass samples of crops that interacted in cassava and samples of yield, then evaluated and analyzed.